The Role of Multicultural Counseling in Addressing Adolescent Identity Challenges in Urban and Rural Areas of Sumatra Province - Hajir Tajiri; Eka Chandra Oktaviani; Muhammad Fajar Abdul Aziz (Universitas PGRI Yogyakarta, 2026)
Indonesia’s multicultural context poses complex challenges for adolescents in constructing their identities, particularly due to unequal social and service conditions between urban and rural areas. Although multicultural counseling has been widely discussed, comparative studies examining contextual differences between urban and rural adolescents in Indonesia remain limited. This study aims to explore the role and strategies of multicultural counseling in addressing adolescent identity challenges across urban and rural settings in Sumatra Province. Using a qualitative descriptive design with a comparative case study approach, data were collected from 45 adolescents in Padang, Bukittinggi, Koto Tangah, and Datar through in-depth interviews, participant observation, and document analysis conducted between February and October 2024. Data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings reveal distinct identity-related challenges across contexts, including a dual identity crisis and social pressure among urban adolescents, as well as access inequality and stigma as major barriers to counseling services in rural areas. These results indicate that adolescent identity challenges differ qualitatively across socio-cultural settings. This study concludes that multicultural counseling should be implemented through contextual and differential strategies tailored to urban and rural needs. Such approaches have important implications for developing community-based mental health counseling policies and services that are culturally responsive in Indonesia. Keywords: adolescent, counseling, multicultural, rural, urban